Estudo genético quantitativo de características andrológicas e de carcaça, medidas in vivo por ultrassonografia, em touros da raça nelore, utilizando inferência bayesiana - LOPES, Dyomar Toledo (2010)
The objective of this study to estimate genetic parameters of traits indicative of male reproductive performance of Nellore to identify the best selection criteria for sperm quality, and check existence of genetic associations among carcass traits, obtained in vivo by ultrasound, and features andrologic. We obtained a measure of scrotal circumference (SC), we calculated the mean testicular volume (VTM), the average testicular weight (PTM), the testicular form (FORM) and has been evaluating the morphology of 1265 Nellore with a mean age of 21 months , animals were classified as suitable or immature (reproductive fitness - AR). There has been assessing housing in vivo by ultrasound, resulting in measures eye area (REA), backfat thickness (EG) and subcutaneous fat thickness in the rump (P8). To estimation of genetic parameters used the Bayesian inference using the software THRGIBBS1F90. The results suggest that selection for PE would not be effective in obtaining genetic gain for semen quality, and in view of its positive association, but of low magnitude, with the seminal qualitative-quantitative aspects. Among all traits, the VTM, PTM and FORM would be more suitable for use as selection criteria when the goal is to achieve genetic progress for semen quality of Nelore bulls because they have a moderate heritability and correlation favorably with the percentage of sperm defects. It is further argued that there are favorable correlated response between reproductive traits and substrate studied, allowing simultaneous genetic progress